Antimicrobial properties of 3D printed biocomposites with heat-treated wood flour using silver nanoparticles with leaf extract. Issue 2 (4th March 2023) - Yurttas, Elif; Tetik, Nurten; Ayrilmis, Nadir
ABSTRACT: Increasing environmental concerns have increased interest in the development of biodegradable materials. In this study, biofilaments for 3D printing were produced with biodegradable polylactic acid (PLA) matrix and modified using wood flour which Liquidambar orientalis leaf extract green synthesized reducing silver nanoparticles and aqueous silver nanoparticles and these filaments are 3D printed. The wood flour and the biocomposite 3D printed were characterized by inductively coupled plasma-optical emission spectrometry (ICP-OES) Analysis and Scanning electron microscope (SEM) techniques. In the antimicrobial test, it was determined that the biocomposites showed antibacterial activity against Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 6538, and the antifungal activity against Candida albicans ATCC 10231. All the biocomposites containing the silver nitrate nanoparticles clearly exhibited the antibacterial properties. The resulting biocomposites were very suitable for biomedical and food industrial applications.